Immune System Effects of Insulin-Like Peptide 5 in a Mouse Model - Vahkal, Brett; Yegorov, Sergey; Onyilagha, Chukwunonso; Donner, Jacqueline; Reddick, Dean; Shrivastav, Anuraag; Uzonna, Jude; Good, Sara V. (Frontiers in Endocrinology, 2021)
Insulin-like peptide 5 (INSL5) is a peptide hormone with proposed actions in glucose homeostasis and appetite regulation via its cognate receptor, relaxin family peptide receptor 4 (RXFP4). Here, we look for evidence for their involvement in the immune system using a mouse model. Methods: In silico analyses: we queried public databases for evidence of expression of INSL5-RXFP4 in immune system tissues/cells (NCBI’s SRA and GeoProfiles) and disorders (EMBO-EBI) and performed phylogenetic footprinting to look for evidence that they are regulated by immune-associated transcription factors (TFs). Experimental analyses: We characterized the expression and correlation of INSL5/RXFP4 and other immune system markers in central and peripheral immune organs from C57/bl6 mice in seven cohorts. We tested whether fluctuations in circulating INSL5 induce an immune response, by injecting mice with 30μg/kg of INSL5 peptide in the peritoneum, and examining levels of immune markers and metabolic peptides in plasma. Lastly, we quantified the expression of Rxfp4 in T-cells, dendritic cells and cell lines derived from human and mouse and tested the hypothesis that co-incubation of ANA-1 cells in INSL5 and LPS alters cytokine expression. Results: We find Insl5 expression only in thymus (in addition to colon) where its expression was highly correlated with Il-7, a marker of thymocyte development. This result is consistent with our in silico findings that Insl5 is highly expressed in thymic DP, DN thymocytes and cortical TEC’s, and with evidence that it is regulated by thymocyte-associated TF’s. We find Rxfp4 expression in all immune organs, and moderately high levels in DCs, particularly splenic DCs, and evidence that it is regulated by immune-associated TF’s, such as STAT’s and GATA. Systemic effects: We observed significantly elevated concentrations of blood GLP-1, GIP, GCG and PYY following intraperitoneal injection of INSL5, and significantly altered expression of cytokines IL-5, IL-7, M-CSF, IL-15, IL-27 and MIP-2. Immune cell effects: Incubation of ANA-1 cells with INSL5 impeded cell growth and led to a transient elevation of IL-15 and sustained reduction in IL-1β, IL-6 and TNFα. Conclusion: We propose that INSL5-RXFP4 play a novel role in both central and peripheral immune cell signaling.